Influence of L-carnitine on growth and plasma IGF-I from gilts harvested at three gestation lengths - K R Brown; B J Johnson; N Z Frantz; R O Gottlob; C N Groesbeck; C W Hastad; C R Neill; J D Schneider; M G Young; J C Woodworth; Robert D Goodband; Michael D Tokach; et al. (Kansas Agricultural Experiment Station Research Reports, 2005)
A total of 59 gilts were used to determine the effects of supplemental L-carnitine on gilt growth and maternal insulin-like growth factor- I (IGF-I). Experimental treatments were arranged in a 2 × 3 factorial with main effects of L-carnitine (0 or 50 ppm) and day of gestation (40, 55, or 70). All gilts received a constant feed allowance of 3.86 lb/day and a topdress containing either 0 or 88 mg of Lcarnitine, starting on the first day of breeding. No differences (P>0.05) between treatments were observed for BW, estimated protein mass, or estimated fat mass at any gestation length. At d 70 of gestation, there was a numeric increase (P>0.10) in BW for the gilts fed L-carnitine, compared with those fed the control diet. At d 40 of gestation, gilts fed Lcarnitine tended to have greater (P = 0.10) backfat, compared with the gilts fed the control diet; but no differences (P>0.05) were observed in backfat on d 0, 55, or 70 of gestation. In addition, no differences (P>0.05) were observed in maternal IGF-I between treatments at any gestation length. Total and free plasma L-carnitine concentrations were similar (P>0.10) at d 0 of gestation, but concentrations were higher (P<0.01) by d 40 of gestation in the gilts fed L-carnitine. These results show that supplemental L-carnitine numerically increases BW of gestating gilts. This data represents the first part of an ongoing study, with the rest of the data being reported in subsequent publications.; Swine Day, 2005, Kansas State University, Manhattan, KS, 2005
Keywords: Swine day; 2005; Summary Publication of Report of Progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 964; Kansas Agricultural Experiment Station contribution; no. 06-63-S; Backfat; Gestation; Gilts; L-carnitine; Pigs; Weight; Swine